Development of Sitophilus granarius (L.), S. oryzae (L.) and S. zeamais Mots. on kernels of Triticum monococcum, T. dicoccum and T. spelta (Bollettino di zoologia agraria e bachicoltura, 2024)
The aim of the present study meant to examine the development ofSitophilus granarius, S. oryzae and S. zeamais on Triticum spelta, T. dicoccumand T. monococcum spikelets and kernels. Absence or poor number of individuals(0-8) on T. spelta and T. dicoccum is observed for all the species. In the case ofT. monococcum spikelets the mean number of emerged adults, even if inferiorthan that one observed on T. dicoccum kernels, ranges from 52 for S. oryzae andS. zeamais to 157 for S. granarius. In fact the kernel is not completely isolatedfrom the outside, as glumes and inner glumes are not contiguos to the kernels. Agreater number of emerged adults is observed on T. spelta kernels, except S.oryzae, where the highest number of individuals occurs on T. dicoccum spikelets.The mean number of individuals emerged from T. monococcum kernels is inferi orthan T. spelta and T. dicoccum kernels. T. monococcum kernels is in fact smaller,about 2/3, than T. spelta and T. dicoccum.In laboratory at 25°C and 70 ± 5% R. H. the beginning of emergence for S.granarius started 33-38 days after egg laying while S. oryzae and S. zeamaisstarted respectively 29-40 and 33-40 after the ovideposition. Also for these speciesthe mean of the development period seems to be significantly shorter for T.dicoccum kernels while the longest period is observed on T. monococcum spikelets.
Keywords: Sitophilus granarius; S. oryzae; S. zeamais; development; Triticum monococcum; T. dicoccum; T. spelta